Penentuan Keputusan Pembelian Singkong Keju di Cikarang Utara Kabupaten Bekasi - Rosdiana Septiani; Fadila Marga Saty; Bina Unteawati (Program Studi Agribisnis, 2022)
This study aims to explain the consumer characteristics of cassava cheese, analyze the influence between price, product quality, service quality and promotion in determining consumer decisions in purchasing cheese cassava and the level of consumer satisfaction. The sampling method was determined by Proportional Cluster Random Sampling, the respondents were 52 consumers of cassava cheese. The data analysis technique used is descriptive analysis, regression analysis, Importance Performance Analysis (IPA) and Net Promoter Score (NPS). The results showed that the characteristics of cassava cheese consumers were 57.69% consisting of women aged 21-25 years, as many as 38.46% working as students had an income of Rp 0-500,000/month. There are 9 levels of consumer satisfaction (affordable prices, prices according to product quality, good taste, suitable for consumption, attractive appearance, satisfactory quality, fast serving, fast serving and friendly with buyers). The NPS value of 36% as many as 24 people means that consumers make repeat purchases and are willing to recommend